2015
DOI: 10.1109/jsen.2015.2469105
|View full text |Cite
|
Sign up to set email alerts
|

Cubature + Extended Hybrid Kalman Filtering Method and Its Application in PPP/IMU Tightly Coupled Navigation Systems

Abstract: Implementing the GPS (Global Positioning System) total carrier phase observations based on the PPP (Precise Point Positioning) technique in a navigation Kalman filter can improve the position accuracy of a GPS/IMU (Inertial Measurement Unit) tightly-coupled navigation system to the sub-meter level. However, the carrier phase implementation introduces extra states like ambiguities, to the Kalman filter state vector, which increases the computational burden especially when nonlinear filtering methods are applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 29 publications
(38 reference statements)
0
18
0
Order By: Relevance
“…From (31) and (35), it can be concluded that all the diagonal elements of ψ i, k are within range (0, 1]. Thus, the weight matrix Ψ k satisfies the inequality:…”
Section: Rmonckf Methodsmentioning
confidence: 98%
“…From (31) and (35), it can be concluded that all the diagonal elements of ψ i, k are within range (0, 1]. Thus, the weight matrix Ψ k satisfies the inequality:…”
Section: Rmonckf Methodsmentioning
confidence: 98%
“…The CKF is used for the forward filtering process of the online CRTSS in this work, which is a second-order approximation to a nonlinear system. 18 Its base principle is to approximate a multidimensional weighted integral by a set of weighted points. 18 The CKF used in this work involves the following recursive relations.…”
Section: The Forward Filtering Processmentioning
confidence: 99%
“…18 Its base principle is to approximate a multidimensional weighted integral by a set of weighted points. 18 The CKF used in this work involves the following recursive relations. In the CKF, cubature points are calculated by the following equations…”
Section: The Forward Filtering Processmentioning
confidence: 99%
“…N real-time target-tracking scenarios, a Kalman filter is widely applied as a linear quadratic estimation method due to its rapid convergence and low need for prior training [1]- [6]. It utilizes a great number of observed measurements, containing statistical noise and other inaccuracies, and computes unknown variables.…”
Section: Introductionmentioning
confidence: 99%